Market Response to Lumpy Skin Disease: Evidence from Indian Dairy Stocks - Banerjee, Arkajit (Indian Journal of Research in Capital Markets, 2025)
Purpose : This study examined whether the 2022 Lumpy Skin Disease outbreak affected the stock prices of Indian dairy firms. Design/Methodology : An event study approach was used with the market model to measure abnormal returns (AR) for four NSE-listed dairy companies over the event window. Findings : None of the firms showed statistically significant AR or cumulative AR during the outbreak period. Practical Implications : The findings indicated that the market did not perceive the outbreak as financially material, suggesting gaps in disease risk communication and investor awareness.